The pro-convulsant effects of diazinon low dose in male rats under amygdala kindling. (4th March 2022) - Saberi, Fatemeh; Bahrami, Farideh; Saberi, Mehdi; Mashhadi Akbar Boojar, Mahdi
Abstract: Organophosphates can damage the brain in systemic intoxication. In this study, the effects of a minimum toxic dose (MTD) of diazinon (DZ) on amygdala afterdischarge threshold (ADT), kindling acquisition and kindled seizure parameters were evaluated. Intact male rats were stereotactically implanted with a tripolar and two monopolar electrodes in the amygdala and dura respectively. After recovery, animals received daily either, olive oil (control), 15 or 30 mg/kg (MTD) of DZ intraperitoneally, and ADT, afterdischarge duration (ADD) at each stage (S1 to S5 ) of kindling and number of trials for kindling acquisition were determined daily. Also, the effect of DZ on stage 4 latency (S4 L), ADD, stage 5 duration (S5 D) and the activity of the red blood cholinesterase (ChE) were evaluated. The ADT was lower and the ADD was longer significantly in DZ treated group in comparison to control ( p < 0.01) and the number of trials to reach each stage of kindling acquisition was reduced ( p < 0.001). The total amount of ADDs during the kindling procedure increased significantly 5 days after DZ treatment. While the S4 L was reduced, the S5 D increased significantly after DZ treatment. The ChE activity was inhibited significantly after 20 min of DZ treatment and continued till 24 h ( p < 0.01). Data indicate that even half of the MTD of DZ could increase the sensitivity and excitability of the CNS to the epileptic activity at least via reduction of stimulation threshold and AD prolongation. Furthermore, repeated exposure to the low concentrations of organophosphates may be pro-convulsant and should be restricted.